Transformasi Digital Manajemen Hafalan Al-Qur’an melalui Pelatihan dan Pendampingan Aplikasi PINT SISWA pada Lembaga Pendidikan Islam - Rifqi, Burhan Nur; Shafwan, Muhammad Hambal (Philosophiamundi, 2025)
Digital transformation in Islamic educational institutions is now a strategic necessity, including in the management of Al-Qur'an memorization. This community service activity was carried out in the form of training and assistance in using the PINT SISWA application at an Islamic educational institution involving tahfidz teachers, application administrators, and institution managers. The results of this community service activity show that training and assistance play an important role in improving teachers' digital literacy, particularly in the use of the PINT SISWA application. Before the training, teachers faced obstacles in the form of limited understanding of digital features, slow data input processes, and dependence on manual reports. The training succeeded in improving the technical competence of teachers, as seen from the increased speed and accuracy of memorization report input, while follow-up mentoring helped minimize usage errors and strengthen reporting consistency. The implementation of the PINT SISWA application also had a significant impact on the quality of Al-Qur'an memorization management through the availability of more accurate, real-time reports that were easily accessible to parents, teachers, and administrators, while also opening up opportunities for the development of Islamic edupreneurs through innovative technology-based educational services